A Compact Single-Feed Patch Antenna with Frequency and Polarization Diversity - Fayyadh Ahmed (Engineering and Technology Journal, 2019)
A new compact single feed square ring patch antenna using meandered 4λ transformer is designed, for frequency and polarization diversity. The proposed antenna is constructed from a square ring patch antenna, and two orthogonal meandered cascaded 4λ transformer (OMCT), incorporated with six switches for frequency and polarization reconfiguration purposes. The OMCT with switches is necessary to get good impedance bandwidth (BW) and axial ratio bandwidth (ARBW) for circular polarization state. In addition, it utilized to excite the antenna at two orthogonal locations, with equal magnitude and quadratic in phase, for achieving circular polarization mode at resonant frequencies 2.44GHz, 4.7GHz, and 5.6GHz. Moreover, it can excite the antenna as non-orthogonal modes for various other frequency bands, such as 2.89 GHz, 3.49 GHz, 4.9 GHz, 5.2GHz, 5.49GHz, 6.16GHz and 3.1GHz as linear polarization (LP) state. The proposed antenna has a compact low profile planar structure with area equal to 23mm2. Simulation and measured results show that the proposed antenna demonstrates a reasonable impedance bandwidth, and axial ratio in the circularly polarized state. Simulation results have been obtained from commercial CST-2014 Microwave Studio. The proposed antenna is fabricated for simulation result verification, and the implemented antenna is tested using R&S ZVL13 Vector Network Analyzer. The experimental confirms the simulation results.